Switchable matched band-stop filter for high power interference mitigation - Adoum, B.A. (2013)
This paper describes an investigation into a novel miniaturized microwave matched band-stop filter with pseudo-infinite attenuation for the enhancement of wireless link on floating production storage and offloading (FPSO) vessels. The proposed method is capable to produce almost infinite attenuation even with very low Q resonator and is suitably used to suppress very high power interference signal. Another important feature of the filter is that it possesses matching response at all frequency. The solution can be easily integrated with the existing system with minimum cost and more importantly without interrupting the service. Furthermore, the filter can be switched to exhibit an all pass response by turning 'OFF' the PIN diodes incorporated into the filter topology. An experimental prototype will be demonstrated for the proof-of-concept. Â© 2013 IEEE.